Serum vitamin A, E and C status in cervical cancer patients undergoing Concurrent Chemo-Radiotherapy, an institutional study - Anju Shrivastava; Satyajit Pradhan; Surendra Pratap Mishra; Anupam Kumar Asthana; Sunil Choudhary; Kulsoom Zahra; Lalit Mohan Aggarwal (Journal of Nutrition & Intermediary Metabolism, 2019)
Vitamin A, E, and C are powerful non enzymatic antioxidants responsible for capturing free radicals, and thus, they prevent oxidative chain reactions. Persistent oxidative stress may cause resistance to apoptosis, which promotes cell proliferation and leads to the tumor and its angiogenesis. Serum level of Vitamin A, E, and C were estimated in carcinoma cervix patients at different phases of treatment and compared it with healthy controls. Ninety-seven histopathologically diagnosed Cervical Carcinoma patients, and thirty age-matched healthy controls were included in this study. Blood samples were taken once from the controls. From each patient undergoing Radiotherapy, four samples were collected i.e., before, during, immediately after and at three months follow-up of treatment. The serum was separated and stored at −20 °C until examination. Statistical analysis was done with the commercial SPSS 21.0 package for Windows (SPSS, IBM Bangalore). P-value < 0.05 was considered statistically significant. Vitamin A, E, and C levels were lower in carcinoma cervix patients of all FIGO (International Federation of Gynecology and Obstetrics) stages compared to controls. Patient serum levels of vitamins decreased again during Concurrent Chemo-Radiotherapy and immediately after the therapy. There is an elevation shown by these vitamins after three months of follow up. The results indicate that the lower serum vitamin A, E, and C levels before treatment could be a cause or an effect of cancer. Further decrease in vitamin levels during and immediately after therapy shows the high oxidative stress during the treatment period, which is beneficial for the patient. These altered vitamin levels were normalized during the time of follow-up. Keywords: Ascorbic acid, α -tocopherol, Carcinoma cervix, Retinol, Oxidative stress